Forms In Visual Types of Modern Chinese Calligraphy - Liu Xiang; Lee, Lilian Shiau Gee (Penerbit UMS, 2022)
Modern calligraphy artworks have presented very strong visual arts attributes over the last few decades, and Chinese modern calligraphy art is no exception to this phenomenon. Chinese modern calligraphy, as a bridge between traditional, Western, modern, and contemporary art, demonstrates a clear relationship and mutual influence between Chinese modern calligraphy and global art. Line has always been the master content of traditional and modern Chinese calligraphy in the formalistic practice of calligraphy art. Recognizing the aesthetic experience requires an understanding of the Chinese concept of line. The author's analysis of lines in this paper is focused on the artworks of Wang Dongling and Qiu Zhenzhong in terms of modern Chinese calligraphy in order to explain divergences from lines in traditional calligraphy and to analyse the strength and emotional expression of the lines in the two artists' works.